Ambulant food vendor's knowledge and practices related to food sanitation procedure - Manalang, Jenny Rose; Reandelar, Joanne F. (2005.)
This qualitative study determined the level of knowledge and the practices on proper hygiene and food preparation sanitation procedures of the ambulant food vendors in a state university. The vendors were purposively chosen to include only the "fishball-cart" vendors who have frying pan on their store area to ensure the availability of raw and cooked products. A test was administered to the vendors to determine their level of knowledge regarding food sanitation procedures. The test was pilot-tested, was examined for content validity, and was item analyzed based on discrimination and item difficulty. The vendors were also observed twice using a violation checklist to describe their food preparation practices. Results revealed a low performance in the test since only 10 (53%) of the vendors passed the test while 9 (47%) failed. There were inconsistencies between knowledge and practice sanitary procedure in food preparation. For instance, most of the vendors (95%) know the proper storage of raw and cooked food but actual observations showed that they did not practice safe food storage. As examined in all cases, when vendors do not know the proper procedure, they also fail to practice it. As an example, the vendors did not really grasp the concept of proper handwashing and did not adequately practice it as well. In general, the vendors observed had been found to have unacceptable practices and thus, an intervention program for behavior modification and information campaign needs to be implemented. The study presented valid evidences of the need for improving food prepares and vendors' knowledge, thus providing a general direction to go home economists for improved services.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Food handling -- Philippines -- Quezon City; Food safety